Interventions to change the behaviour of health professionals and the organisation of care to promote weight reduction in children and adults with overweight or obesity - Flodgren, G; Gonçalves-Bradley, D; Summerbell, C (Wiley, 2017)
Background The prevalence of overweight and obesity is increasing globally, an increase which has major implications for both population health and costs to health services. This is an update of a Cochrane Review. Objectives: To assess the effects of strategies to change the behaviour of health professionals or the organisation of care compared to standard care, to promote weight reduction in children and adults with overweight or obesity. Search methods: We searched the following databases for primary studies up to September 2016: CENTRAL, MEDLINE, Embase, CINAHL, DARE and PsycINFO. We searched the reference lists of included studies and two trial registries. Selection criteria: We considered randomised trials that compared routine provision of care with interventions aimed either at changing the behaviour of healthcare professionals or the organisation of care to promote weight reduction in children and adults with overweight or obesity. Data collection and analysis: We used standard methodological procedures expected by Cochrane when conducting this review. We report the results for the professional interventions and the organisational interventions in seven 'Summary of findings' tables. Main results: We identified 12 studies for inclusion in this review, seven of which evaluated interventions targeting healthcare professional and five targeting the organisation of care. Eight studies recruited adults with overweight or obesity and four recruited children with obesity. Eight studies had an overall high risk of bias, and four had a low risk of bias. In total, 139 practices provided care to 89,754 people, with a median follow‐up of 12 months. Professional interventions: Educational interventions aimed at general practitioners (GPs), may slightly reduce the weight of participants (mean difference (MD) ‐1.24 kg, 95% confidence interval (CI) ‐2.84 to 0.37; 3 studies, N = 1017 adults; low‐certainty evidence). Tailoring interventions to improve GPs' compliance with obesity guidelines probably leads to little or no difference in weight loss (MD 0.05 (kg), 95% CI ‐0.32 to 0.41; 1 study, N = 49,807 adults; moderate‐certainty evidence). It is uncertain if providing doctors with reminders results in a greater weight reduction than standard care (men: MD ‐11.20 kg, 95% CI ‐20.66 kg to ‐1.74 kg, and women: MD ‐1.30 kg, 95% CI [‐7.34, 4.74] kg; 1 study, N = 90 adults; very low‐certainty evidence). Providing clinicians with a clinical decision support (CDS) tool to assist with obesity management at the point of care leads to little or no difference in the body mass index (BMI) z‐score of children (MD ‐0.08, 95% CI ‐0.15 to ‐0.01 in 378 children; moderate‐certainty evidence), CDS tools may lead to little or no difference in weight loss in adults: MD ‐0.095 kg (‐0.21 lbs), P = 0.47; 1 study, N = 35,665; low‐certainty evidence. Organisational interventions: Adults with overweight or obesity may lose more weight if the care was provided by a dietitian (by ‐5.60 kg, 95% CI ‐4.83 kg to ‐6.37 kg) or by a doctor‐dietitian team (by ‐6.70 kg, 95% CI ‐7.52 kg to ‐5.88 kg; 1 study, N = 270 adults; low‐certainty evidence). Shared care leads to little or no difference in the BMI z‐score of children with obesity (adjusted MD ‐0.05, 95% CI ‐0.14 to 0.03; 1 study, N = 105 children; low‐certainty evidence). Organisational restructuring of the delivery of primary care (i.e. introducing the chronic care model) may result in a slightly lower increase in the BMI of children who received care at intervention clinics (BMI change: adjusted MD ‐0.21, 95% CI ‐0.50 to 0.07; 1 study, unadjusted MD ‐0.18, 95% CI ‐0.20 to ‐0.16; N=473 participants; moderate‐certainty evidence). Mail and phone interventions probably lead to little or no difference in weight loss in adults (mean weight change (kg) using mail: ‐0.36, 95% CI ‐1.18 to 0.46; phone: ‐0.44, 95% CI ‐1.26 to 0.38; 1 study, N = 1801 adults; moderate‐certainty evidence). Care delivered by a nurse at a primary care clinic may lead to little or no difference in the BMI z‐score in children (MD ‐0.02, 95% CI ‐0.16 to 0.12; 1 study, N = 52 children; very low‐certainty evidence). Two studies reported data on cost effectiveness: one study favoured mail and standard care over telephone consultations, and the other study achieved weight loss at a modest cost in both intervention groups (doctor and doctor‐dietitian). One study of shared care reported similar adverse effects in both groups. Authors' conclusions: We found little convincing evidence for a clinically‐important effect on participants' weight or BMI of any of the evaluated interventions. While pooled results from three studies indicate that educational interventions targeting healthcare professionals may lead to a slight weight reduction in adults, the certainty of these results is low. Two trials evaluating CDS tools (unpooled results) for improved weight management suggest little or no effect on weight or BMI change in adults or children with overweight or obesity. Evidence for all the other interventions evaluated came mostly from single studies. The certainty of the included evidence varied from moderate to very low for the main outcomes (weight and BMI). All of the evaluated interventions would need further investigation to ascertain their strengths and limitations as effective strategies to change the behaviour of healthcare professionals or the organisation of care. As only two studies reported on cost, we know little about cost effectiveness across the evaluated interventions.